A Descriptive Study on Reading Comprehension on Descriptive Text of The Seventh Grade Students at SMP Negeri 2 Rogojampi in The Academic Year 2013/2014 - Irawati, Irawati (LUNAR, 2017)
The main purpose of conducting this research was to measure how far the reading comprehension in descriptive text of the seventh grade students of SMP Negeri 2 Rogojampi in academic year 2013/2014. There are three indicators in this research. Those are comprehending words, comprehending sentences, and comprehending paragraphs. In this research, the researcher used descriptive quantitative research. The data was in the form of student’s reading comprehension score. The instrument that is used in this research is a test. The kind of the test that used is multiple choice test. There are 20 items in the test covering identifying synonym, identifying reference, comprehending sentences, identifying main idea, and identifying the topic. The score for each item is 5 and the maximal score is 100. From the data analysis of the research findings and discussions, the researcher found the minimum score is 50 and the maximum score is 95. The average or mean of student’s reading comprehension score is 75.98%. It was in the range between71–80. It means that in general, the student’s reading comprehension on descriptive text was good. The students’ reading comprehension on descriptive text in comprehending words was 81.2%. It was in the range between 81 – 90. It can be said that the students reading comprehension in comprehending words was very good. The students’ reading comprehension on descriptive text in comprehending sentences was 81.5%. It was in the range between81–90. It can be said that the students reading comprehension in comprehending sentences was very good. The students’ reading comprehension on descriptive text in comprehending paragraphs was 63.9%. It was in the range between61–70. It can be said that the students reading comprehension in comprehending paragraphs was more than enough. There are some suggestion given to the English teacher, the students and the other researcher. (1) The teacher should use the information about their student’s reading comprehension on descriptive text as reflection to overcome their student’s problems. The English teacher should find an effective way on their teaching learning process to increase the student’s reading achievement. (2) The students should learn more about reading comprehension, especially in comprehending words, comprehending sentences, and comprehending paragraphs. (3) For the other researcher, it can be used as the basic for conducting experimental research or classroom action research to solve the student’s reading comprehension problems, especially for comprehending paragraphs.